FgBUD14 is important for ascosporogenesis and involves both stage‐specific alternative splicing and RNA editing during sexual reproduction. (9th March 2021) - Liang, Jie; Fu, Xianhui; Hao, Chaofeng; Bian, Zhuyun; Liu, Huiquan; Xu, Jin‐Rong; Wang, Guanghui
Summary: In wheat head blight fungus Fusarium graminearum, A‐to‐I RNA editing occurs specifically during sexual reproduction. Among the genes with premature stop codons (PSCs) that require RNA editing to encode full‐length proteins, FgBUD14 also had alternative splicing events in perithecia. In this study, we characterized the functions of FgBUD14 and its post‐transcriptional modifications during sexual reproduction. The Fgbud14 deletion mutant was slightly reduced in growth, conidiation and virulence. Although deletion of FgBUD14 had no effect on perithecium morphology, the Fgbud14 mutant was defective in crozier formation and ascus development. The FgBud14‐GFP localized to the apex of ascogenous hyphae and croziers, which may be related to its functions during early sexual development. During vegetative growth and asexual reproduction, FgBud14‐GFP localized to hyphal tips and both ends of conidia. Furthermore, mutations blocking the splicing of intron 2 that has the PSC site had no effect on the function of FgBUD14 during sexual reproduction but caused a similar defect in growth with Fgbud14 mutant. Expression of the non‐editable FgBUD14 Intron2‐TAA mutant allele also failed to complement the Fgbud14 mutant. Taken together, FgBUD14 plays important roles in ascus development, and both alternative splicing and RNA editing occur specifically to its transcripts during sexual reproduction in F . graminearum .